Peran Kepuasan Pelanggan Memediasi Product Quality dan Green Marketing terhadap Loyalitas Pelanggan Kopi Kenangan - Salsabila; Nel Arianty; Irma Christiana (MOTIVASI, 2026)
Purpose– This research is motivated by the increasing environmental issues and the importance of customer loyalty, where there is still a gap between product quality and the implementation of green marketing at Kopi Kenangan in Medan. This study aims to analyze the effect of product quality and green marketing on customer loyalty, with customer satisfaction as an intervening variable. Design/methodology– The research method uses a quantitative approach with data from 100 respondents via questionnaires, and is analyzed using PLS-SEM with the help of SmartPLS, including outer model, inner model, and hypothesis tests. Findings- The results of the study showed that product quality had no significant effect on customer satisfaction or loyalty, while green marketing and customer satisfaction had a significant effect on loyalty. Furthermore, customer satisfaction did not mediate the effect of product quality, but it did mediate the effect of green marketing, so loyalty was more influenced by green marketing and customer satisfaction.